A feasibility study of the effects of implementing a staff-level recovery-oriented training intervention in older people's mental health services. (1st November 2020) - Daley, Stephanie; Slade, Mike; Dewey, Michael; Banerjee, Sube
Abstract: Objectives: The concept of recovery has exerted considerable traction in mental health services for adults of working age, but less so in older people's mental health services. The aim of this study was to evaluate the feasibility of a staff-level recovery intervention in older people's mental health services. Method: The study used a mixed-method pre-post design. The study took place in NHS older people's mental health services, UK. Staff participants were multi-disciplinary mental health team members from the same service. The intervention was a manualised staff-level recovery intervention called the Older Adults Recovery Intervention (OARI). Measurement included the Recovery Knowledge Inventory and the Recovery Attitudes Questionnaire (RAQ-7) as well as fidelity data and in-depth qualitative interviews. Results: OARI was delivered to 204 staff in 15 clinical teams. There was a statistically significant change towards improvement in four of the six recovery attitude and knowledge sub-scales. There were positive findings in change in practice at individual level, but not at team level. A number of context barriers were identified leading to the intervention not being delivered as intended. Conclusions: Further development of OARI will involve a clearer distinction about the practice implications for service users with dementia versus functional illnesses, a stronger focus on implementation support, more use of evidence in training materials and a tailoring of context to meet professional group training needs. Overall, this study contributes novel data to the evidence base for recovery within older people's mental health services.